1984
DOI: 10.1037/0278-7393.10.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Role of feedback, category size, and stimulus distortion on the acquisition and utilization of ill-defined categories.

Abstract: The magnitude, efficiency, and scope of learning ill-defined categories without feedback training were investigated for a wide range of stimulus-distortion conditions. In Experiment 1, subjects classified either low-, medium-, high-, or mixed-level distortions under feedback or no-feedback training and then received a common transfer test containing old, new, prototype, and unrelated stimuli. In Experiment 2, the training patterns were multidimensionally scaled, and a measure of categorical structure was deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 22 publications
6
90
0
1
Order By: Relevance
“…That is, an unsupervised form of category learning seems to be overlaid on the representation that evolved during supervised training. These results, therefore, corroborate findings from the unsupervised category literature that suggest that people make use of inherent category structure without the aid of feedback (Ahn & Medin, 1992;Clapper & Bower, 1994;Gureckis & Love, 2003;Homa & Cultice, 1984;Wills & McLaren, 1998). The novelty in these results is that they demonstrate that the unsupervised learning occurs even after the formal training stage in this paradigm.…”
Section: Discussionsupporting
confidence: 81%
“…That is, an unsupervised form of category learning seems to be overlaid on the representation that evolved during supervised training. These results, therefore, corroborate findings from the unsupervised category literature that suggest that people make use of inherent category structure without the aid of feedback (Ahn & Medin, 1992;Clapper & Bower, 1994;Gureckis & Love, 2003;Homa & Cultice, 1984;Wills & McLaren, 1998). The novelty in these results is that they demonstrate that the unsupervised learning occurs even after the formal training stage in this paradigm.…”
Section: Discussionsupporting
confidence: 81%
“…Ashby, Queller, and Berretty (1999) showed that participants initially opt for unidimensional solutions (ignoring every dimension of variation but one) but can be brought to entertain multidimensional solutions with the aid of supervision. Several other studies also have shown the preference for the use of one dimension (Love, 2002) or of category structures with minor prototype distortions (Homa & Cultice, 1984). As stated previously, most of the evidence supporting these generalizations derives from experiments testing simple visual categories in which the dimensions of variation are readily identifiable to participants.…”
mentioning
confidence: 80%
“…Although unsupervised learning has not been as extensively studied as supervised learning, people can learn without external feedback (Homa & Cultice, 1984). One important challenge is to characterize how humans build internal representations in the absence of explicit feedback.…”
Section: Modeling Unsupervised Learningmentioning
confidence: 99%